Analisis Hujan Dan Angin Kencang Di Melawi Menggunakan Data Radar Dan Satelit Cuaca (Studi Kasus Tanggal 29 Desember 2018) - Efendi, Ajis Nur; Kuncorojati, Siwi (Jurnal Widya Climago, 2020)
On 29 December 2018, heavy rain and strong winds damaged around 100 houses and public facilities in the Pelempai Jaya village and Nanga ella, Melawi District, Ella Hilir Subdistrict. The incident happened at around 16.30 WIB, author do an analysis to find out the causes and the patterns. The research method used by the authors is utilizing dual-polarization weather radar data, satellite imagery of himawari satellites and weather phenomena using Madden Jullian Oscillation (MJO), the Streamline air pressure patterns. The results of the analysis showed that during the incident, Data MJO is at phase 5, there were low pressure patterns in the northern and southern regions of Indonesia. From the weather radar and satellite data, detected the presence of clouds Cumulunimbus moving towards the east with fast movement, wind speed data from the radar showed more than 20 m/s. The reflectivity value of the Cmax product showed the value of 50 – 60 dBz. Cloud peak temperature from weather, the value has decreased significantly when events from -220C to -650C. It can be concluded that, rain and strong winds are caused by the presence of clouds cumulunimbus whose formation can be described well by radar and weather satellites.